Attenuation of ketamine-induced impairment in verbal learning and memory in healthy volunteers by the AMPA receptor potentiator PF-04958242 - Ranganathan, M; DeMartinis, N; Huguenel, B; Gaudreault, F; Bednar, M M; Shaffer, C L; Gupta, S; Cahill, J; Sherif, M A; Mancuso, J; Zumpano, L; D’Souza, D C (Molecular psychiatry, 2017)
There is a need to develop treatments for cognitive impairment associated with schizophrenia (CIAS). The significant role played by N -methyl- d -aspartate receptors (NMDARs) in both the pathophysiology of schizophrenia and in neuronal plasticity suggests that facilitation of NMDAR function might ameliorate CIAS. One strategy to correct NMDAR hypofunction is to stimulate α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) as AMPAR and NMDAR functioning are coupled and interdependent. In rats and nonhuman primates (NHP), AMPAR potentiators reduce spatial working memory deficits caused by the nonselective NMDAR antagonist ketamine. The current study assessed whether the AMPAR potentiator PF-04958242 would attenuate ketamine-induced deficits in verbal learning and memory in humans. Healthy male subjects ( n =29) participated in two randomized treatment periods of daily placebo or PF-04958242 for 5 days separated by a washout period. On day 5 of each treatment period, subjects underwent a ketamine infusion for 75 min during which the effects of PF-04958242/placebo were assessed on ketamine-induced: (1) impairments in verbal learning and recall measured by the Hopkins Verbal Learning Test; (2) impairments in working memory on a CogState battery; and (3) psychotomimetic effects measured by the Positive and Negative Syndrome Scale and Clinician-Administered Dissociative Symptoms Scale. PF-04958242 significantly reduced ketamine-induced impairments in immediate recall and the 2-Back and spatial working memory tasks (CogState Battery), without significantly attenuating ketamine-induced psychotomimetic effects. There were no pharmacokinetic interactions between PF-04958242 and ketamine. Furthermore, PF-04958242 was well tolerated. ‘High-impact’ AMPAR potentiators like PF-04958242 may have a role in the treatment of the cognitive symptoms, but not the positive or negative symptoms, associated with schizophrenia. The excellent concordance between the preclinical (rat, NHP) and human studies with PF-04958242, and in silico modeling of AMPAR–NMDAR interactions in the hippocampus, highlights the translational value of this study.